2021
DOI: 10.5501/wjv.v10.i4.137
|View full text |Cite
|
Sign up to set email alerts
|

Hypotheses and facts for genetic factors related to severe COVID-19

Abstract: Genome-wide association analysis allows the identification of potential candidate genes involved in the development of severe coronavirus disease 2019 (COVID-19). Hence, it seems that genetics matters here, as well. Nevertheless, the virus's nature, including its RNA structure, determines the rate of mutations leading to new viral strains with all epidemiological and clinical consequences. Given these observations, we herein comment on the current hypotheses about the possible role of the genes in association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 127 publications
(169 reference statements)
2
12
0
Order By: Relevance
“…Likewise, another study identified two mutations in males with severe COVID-19 - a missense variant (c.2383G>T; p.[Val795Phe]) and a deletion variant (c.2129_2132del; p.[Gln710Argfs*18]), attributing the decreased number of IFN production to the lower expression of TLR7 ( van der Made et al, 2020 ). These deficiencies significantly impact males due to hemizygosity on the X chromosome ( Kotsev et al, 2021 ). Furthermore, TIRAP corresponds to the TLR/IL-1 receptor complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, another study identified two mutations in males with severe COVID-19 - a missense variant (c.2383G>T; p.[Val795Phe]) and a deletion variant (c.2129_2132del; p.[Gln710Argfs*18]), attributing the decreased number of IFN production to the lower expression of TLR7 ( van der Made et al, 2020 ). These deficiencies significantly impact males due to hemizygosity on the X chromosome ( Kotsev et al, 2021 ). Furthermore, TIRAP corresponds to the TLR/IL-1 receptor complex.…”
Section: Discussionmentioning
confidence: 99%
“…The IFI30 rs11554159 polymorphism is linked with increased susceptibility and severe outcome of COVID-19 due to high viral charge ( Monticelli et al, 2021 ). Moreover, Interferon Induced Transmembrane Protein 3 ( IFITM3 ) polymorphisms were also associated with a higher disease burden and a greater risk of acquiring SARS-CoV-2 infection ( Gómez et al, 2021 , Iyer et al, 2020 , Kotsev et al, 2021 , Zhang, Q., Bastard, P., Liu, Z., Le Pen, J., Moncada-Velez, M., Chen, J., Ogishi, M., Sabli, I.K.D., Hodeib, S., Korol, C., Rosain, J., Bilguvar, K., Ye, J., Bolze, A., Bigio, B., Yang, R., Arias, A.A., Zhou, Q., Zhang, Y., Onodi, F., Korniotis, S., Karpf, L., Philippot, Q., Chbihi, M., Bonnet-Madin, L., Dorgham, K., Smith, N., Schneider, W.M., Razooky, B.S., Hoffmann, H.-H., Michailidis, E., Moens, L., Han, J.E., Lorenzo, L., Bizien, L., Meade, P., Neehus, A.-L., Ugurbil, A.C., Corneau, A., Kerner, G., Zhang, P., Rapaport, F., Seeleuthner, Y., Manry, J., Masson, Cecile, Schmitt, Yohann, Schlüter, A., Le Voyer, T., Khan, T., Li, J., Fellay, J., Roussel, L., Shahrooei, Mohammad, Alosaimi, M.F., Mansouri, Davood, Al-Saud, H., Al-Mulla, F., Almourfi, F., Al-Muhsen, S.Z., Alsohime, F., Al Turki, S., Hasanato, R., van de Beek, D., Biondi, A., Bettini, L.R., D’Angio’, M., Bonfanti, P., Imberti, L., Sottini, A., Paghera, S., Quiros-Roldan, E., Rossi, C., Oler, A.J., Tompkins, M.F., Alba, C., Vandernoot, I., Goffard, J.-C., Smits, G., Migeotte, I., Haerynck, F., Soler-Palacin, P., Martin-Nalda, A., Colobran, R., Morange, P.-E., Keles, S., Çölkesen, F., Ozcelik, T., Yasar, K.K., Senoglu, S., Karabela, Ş.N., Rodríguez-Gallego, C., Novelli, G., Hraiech, S., Tandjaoui-Lambiotte, Y., Duval, X., Laouénan, C., COVID-STORM Clinicians, COVID Clinicians, Imagine COVID Group, French COVID Cohort Study Group, CoV-Contact Cohort, Amsterdam UMC Covid-19 Biobank, COVID Human Genetic Effort, NIAID-USUHS/TAGC COVID Immunity Group, Snow, A.L., Dalgard, C.L., Milner, J.D., Vinh, D.C., Mogensen, T.H., Marr, N., Spaan, A.N., Boisson, B., Boisson-Dupuis, S., Bustamante, J., Puel, A., Ciancanelli, M.J., Meyts, I., Maniatis, T., Soumelis, V., Amara, A., Nussenzweig, M., García-Sastre, A., Krammer, F., Pujol, A., Duffy, D., Lifton, R.P., Zhang, S.-Y., Gorochov, G., Béziat, V., Jouanguy, E., Sancho-Shimizu, V., Rice, C.M., Abel, L., Notarangelo, L.D., Cobat, A., Su, H.C., Casanova, J.-L., Foti, G., Bellani, G., Citerio, G., Contro, E., Pesci, A., Valsecchi, M.G., Cazzaniga, M., Abad, J., Aguilera-Albesa, S., Akcan, O.M., Darazam, I.A., Aldave, J.C., Ramos, M.A., Nadji, S.A., Alkan, G., Allardet-Servent, J., Allende, L.M., Alsina, L., Alyanakian, M.-A., Amador-Borrero, B., Amoura, Z., Antolí, A., Arslan, S., Assant, S., Auguet, T., Azot, A., Bajolle, F., Baldolli, A., Ballester, M., Feldman, H.B., Barrou, B., Beurton, A., Bilbao, A., Blanchard-Rohner, G., Blanco, I., Blandinières, A., Blazquez-Gamero, D., Bloomfield, M., Bolivar-Prados, M., Borie, R., Bosteels, C., Bousfiha, A.A., Bouvattier, C., Boyarchuk, O., Bueno, M.R.P., Bustamante, J., Cáceres Agra, J.J., Calimli, S., Capra, R., Carrabba, M., Casasnovas, C., Caseris, M., Castelle, M., Castelli, F., de Vera, M.C., Castro, M.V., Catherinot, E., Chalumeau, M., Charbit, B., Cheng, M.P., Clavé, P., Clotet, B., Codina, A., Colkesen, F., Çölkesen, F., Colobran, R., Comarmond, C., Dalmau, D., Darley, D.R., Dauby, N., Dauger, S., de Pontual, L., Dehban, A., Delplancq, G., Demoule, A., Diehl, J.-L., Dobbelaere, S., Durand, S., Eldars, W., Elgamal, M., Elnagdy, M.H., Emiroglu, M., Erdeniz, E.H., Aytekin, S.E., Euvrard, R., Evcen, R., Fabio, G., Faivre, L., Falck, A., Fartoukh, M., Faure, M., Arquero, M.F., Flores, C., Francois, B., Fumadó, V., Fusco, F., Solis, B.G., Gaussem, P., Gil-Herrera, J., Gilardin, L., Alarcon, M.G., Gi...…”
Section: Discussionmentioning
confidence: 99%
“…Interferon-induced transmembrane protein-3 (IFITM3) protein also causes alteration of lipid/cholesterol content and curvature of endosomal membrane that in turn increases pH of endosomal contents, which favors killing of the virus [14]. Three single nucleotide polymorphisms (SNPs) of IFITM3 gene rs34481144, rs6598045, and rs12252 (c. 42 T/C) were found to be associated in COVID-19 infection [15]. rs34481144 and rs6598045 SNPs are located in the 5′ untranslated region (5′-UTR) and proximal promoter, respectively, whereas rs12252 (c. 42 T/C) SNP is located in the coding region (Exon-1) and can significantly alter the expression level of the IFITM3 protein.…”
Section: Open Accessmentioning
confidence: 99%
“…Recent GWAS of COVID-19 susceptibility and severity [27][28][29] have identified SNPs in several loci on chromosomes 3, 9 and 21. 30 Using our eQTL resource in conjunction with COVID-19 GWAS, we conducted MR analyses that identified seven genes, including OAS1 and IFNAR2, as putatively causal for COVID-19 severity. The OAS1/2/3 cluster has been identified as a risk locus for COVID-19 severity.…”
Section: Discussionmentioning
confidence: 99%